Legal Risk Analysis in the Sharia Bank Operational System - Alfiatun Zahrah; Suci Mardiyah; Muhammad Syaipudin; Saru Reza (Journal of Financial and Business, 2025)
This study analyzes legal risks in the operational system of Islamic banks, with the aim of identifying factors that can affect legal compliance and their implications for the stability of Islamic banking. Islamic banks operate based on sharia principles as stated in national regulations and fatwas of the National Sharia Council (DSN), so that potential legal risks can arise due to inconsistencies in products and services with sharia provisions, changes in regulations, and lack of legal understanding by stakeholders. This study uses a qualitative method with an analysis of Islamic banking regulations, case studies of legal disputes, and interviews with practitioners and regulators. The results of the study indicate that strengthening compliance with sharia regulations and harmonization between positive law and Islamic law are key to mitigating legal risks. In addition, increasing contract transparency, legal education for industry players, and the active role of supervisory authorities can increase the effectiveness of the operational system of Islamic banks. Thus, this study provides strategic recommendations for Islamic banks in managing legal risks in order to maintain the sustainability and trust of customers in the Islamic banking industry.